How Often Does the Exchange Rate Granger Cause the Stock Market in Pakistan? A Bootstrap Rolling Window Approach - Khan, Khalid; SU, Chi-Wei; Khurshid, Adnan; Rehman, Ashfaq U. (Asian Journal of Applied Economics, 2018)
This paper investigates the causal link between the stock market (SM) and the exchange rate (EXR) in Pakistan, using the bootstrap Granger causality and sub-sample rolling window estimation. The full sample Granger causality test indicates no causality between the SM and the EXR. The stability of the parameters is examined by taking into the account structural changes for individual series as well as the VAR. The full sample Granger test shows the absence of causality. The rolling window approach shows the uni-directional positive and negative relationship between the SM and the EXR. The study gives some suggestions to the government and policy makers that a well-coordinated policy implementation and execution regarding the SM and the EXR are crucial in attracting foreign investors and developing a sound financial system in the country complementary to the development of the economy.